THE CONVERSATIONAL IMPLICATURES IN FILM “THE VOW” BASED ON GRICE’S COOPERATIVE PRINCIPLE AND IT’S MAXIMS - Daniar Sofeny (Edulitics (Education, Literature, and Linguistics) Journal, 2016)
It is widely argued that Grice’s theory of implicature has wide anduseful applications. Based on Grice’s Cooperative Principle and its maxims, thisstudy attempts to analyze pragmatically the conversational implicatures in film“The Vow”. The result shows that in the conversation, the four maxim areflouted. The maxims of Quantity (2, 86%) the highest score. 13 out of 22dialogues flouted this maxim. The second frequently flouted are the maxim ofrelevance and manner (1, 6%), and then followed by maxim of quality (1, 54%).These maxims are considered to be flouted based on the category and thecharacteristic given by Grice (1967). In this analysis, I argue that the step-by stepreasoning rigor of the CP and its maxims is worth being inspected by linguistsin general and pragmatiticists in particular. Keywords: cooperative principle and its maxims, conversational implicatures.